2019
DOI: 10.1556/034.61.2019.3-4.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA extraction methods from Geranium (Geraniaceae)

Abstract: The genus Geranium (Geraniaceae); with about 320 species throughout the temperate regions, is chemically characterised by the presence of tannins, flavonoids, anthocyanins and essential oils which interfere with the extraction of pure genomic DNA. It is necessary to optimise the extraction protocols to reduce the effects of the presence of these compounds to the lowest level. The present study compares the plant genomic DNA extraction Kit (DNP TM Kit), CTAB DNA extraction method by Murray and Thompson and Sahu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
(45 reference statements)
0
34
0
Order By: Relevance
“…These were dried by silica gel powder. CTAB activated char-coal protocol was used to extract genomic DNA (Esfandani- Bozchaloyi et al 2019). The quality of extracted DNA was examined by running on 0.8% agarose gel.…”
Section: Dna Extraction and Issr Assaymentioning
confidence: 99%
“…These were dried by silica gel powder. CTAB activated char-coal protocol was used to extract genomic DNA (Esfandani- Bozchaloyi et al 2019). The quality of extracted DNA was examined by running on 0.8% agarose gel.…”
Section: Dna Extraction and Issr Assaymentioning
confidence: 99%
“…Leaves were dried. DNA extraction was carried out according to the previous protocol (ESFANDANI-BOZCHALOYI et al, 2019). DNA quality was checked on an agarose gel to confirm the purity.…”
Section: Random Amplified Polymorphic Dnamentioning
confidence: 99%
“…These were dried by silica gel powder. CTAB activated charcoal protocol was used to extract genomic DNA (Esfandani-Bozchaloyi et al, 2019). The quality of extracted DNA was examined by running it on 0.8% agarose gel.…”
Section: Dna Extraction and Issr Assaymentioning
confidence: 99%
“…Recent ISSR studies of natural populations have demonstrated the hypervariable nature of these markers and their potential use for population-level studies (Hulte´n and Fries, 1986). Limitations of the ISSR technique, as is the case for Random Amplification of Polymorphic DNA (RAPD; Esfandani-Bozchaloyi et al, 2019), are that the bands are scored as dominant markers and the genetic diversity estimates are based on diallelic characters. In the present study, ISSR markers were employed to analyze genetic diversity in 110 E. ciconium accessions belonging to 15 different populations for the first time in the Iran.…”
Section: Introductionmentioning
confidence: 99%